Sistem Autopoiesis dalam Implementasi Projek Penguatan Profil Pelajar Pancasila di Sekolah Menengah Atas Kota Surakarta - Muhammad Irsandhi, Marcel; Atik Catur Budiati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The implementation process of the Pancasila Student Profile Strengthening Project (P5) must be carried out independently and centered on students. Schools have the task of creating effective learning designs. The purpose of this study was to determine the school's adaptation in recognizing potential, obstacles, and strategies during the P5 program using Niklas Luhman's autopoiesis system theory. This study uses a qualitative method with a phenomenological approach. Data sources come from interviews, observations, and document analysis. Data validity uses triangulation of sources and techniques. Data analysis in this study uses the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study explain that the potential, obstacles, and strategies carried out by schools are a depiction of autopoiesis in the implementation of the P5 program. This is because each characteristic of autopoiesis is found in every element used by the school, including the formation of school elements, how to organize, system references, and systems applied in the implementation of the P5 program.